The Effects of Chlorhexidine Dressing on Health Care-Associated Infection in Hospitalized Patients: A Meta-Analysis - Hou-Xing WANG; Shu-Yuan XIE; Hao WANG; Hao-Kai CHU (Tehran University of Medical Sciences, 2019)
Background: To assess the effects of chlorhexidine dressing on health care-associated infection in hospitalized patients. Methods: We searched for English-language published randomized controlled trials (RCTs) in Cochrane Library, EMBASE and PubMed between January 1998 and January 2018. We used meta-analysis to calculate the risk ratios (RRs) and 95% confidence intervals (CIs) of the data, and using the I2 assessment to summarize the heterogeneity of RCTs and the funnel plot and Egger regression test to evaluate publication bias. Results: A total of 13 RCTs were included in our meta-analysis, including 7555 patients and 11,931 catheters. The effects of chlorhexidine dressing on the incidence of catheter-related bloodstream infections (CRBSIs) were reported in 13 RCTs, and the incidence of CRBSIs were 1.3% (80/6160) in the chlorhexidine group and 2.5% (145/5771) in the control group. We used a forest plot to determine the risk ratio (RR) of chlorhexidine dressing on the incidence of CRBSIs, and our results showed that chlorhexidine dressing significantly reduced the incidence of CRBSIs (RR 0.55, 95% CI 0.39-0.77, P<0.001). Moreover, we also analyzed the effects of chlorhexidine dressing on the incidence of catheter colonization and catheter-related infections (CRIs), and our forest plot results showed that chlorhexidine dressing significantly reduced the incidence of catheter colonization (RR 0.52, 95% CI 0.40-0.67, P<0.001) and the incidence of CRIs (RR 0.43, 95% CI 0.28-0.66, P<0.001) in hospitalized patients. Conclusion: The use of chlorhexidine dressings for hospitalized patients significantly reduce the incidence of CRBSIs, catheter colonization and CRIs.